Digital elevation models constructed from JARE aerial photographs ... - Hata, Shuntaro; Kawamata, Moto; Doi, Koichiro (Arctic Data archive System (ADS), Japan, 2023)
This is a dataset forthe dataset for timeseries of surface elevation and volume of LKI(Lake Kaminotani-Ike). ...